Tatak Pilipino [episode no. 33]. ([Quezon City ABS-CBN, 1991)
A unique display of Pilipino ways and style.
Gay images on film (20 min.) -- Homosexual relationships (10 min.) -- Gay lingo (15 min.) -- Lesbianism (10 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Gays -- Philippines; Homosexuality -- Philippines; Lesbianism